The Role of Work Motivation on the Effect of Education, Training and Competency on Employee Performance - Sutianingsih, Sutianingsih; Fachrurrosar Widodo, Galih (JOURNAL OF ADVANCED STUDIES IN MANAGEMENT, 2024)
This research aims to analyze the influence of training and competency education on performance through work motivation at PT Branch Offices. BRI Sragen. The analysis techniques used are regression analysis, path analysis, t test. Conclusion: Training education has a positive and significant impact on motivation. Competence has a negative and significant effect on motivation. Training education has a positive and insignificant effect on employee performance. Competency has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance. Work motivation can strengthen the influence of education, training and competency on employee performance Keywords—Competence; Education Training; Motivation; Performance